CPWF Annual Report 2009 - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2010)
The CPWF was designed to be different. Developed in response to a call for change in a previous round of Consultative Group on International Agricultural Research (CGIAR) system reform, the CPWF was intended to foster cross-CGIAR cooperation and find ways to bring in new partners. Over time the CPWF has successfully broadened the CGIAR’s sources of innovative research on water and food. Through its broad partnerships, the program conducts research that leads to positive impact on the poor and to policy change. The CPWF does this by focusing research on the intersection of poverty, water and food and then linking relevant research outputs with the broader development community. This implies working in a way that emphasizes: l integrated and participatory research; l strategic planning and decision making across scales to support efficiency and effectiveness of outputs and outcomes delivery; and l a partnership approach to research design, implementation and uptake of outputs that involves key stakeholders and builds capacity.